THE EFFECT OF BI RATE, EXCHANGE RATE, AND WORLD OIL PRICES ON GREEN INVESTMENT IN INDONESIA - Yulia Risma; Weri; Miksalmina; Talbani Farlian; Cut Zakia Rizki; Fakhruddin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines how monetary policy and external shocks influence green investment in Indonesia, proxied by the SRI-KEHATI Index. Drawing on the perspective of asset pricing theory, macroeconomic variables are treated as systematic factors affecting sustainable stock performance. Using monthly data from 2007-2024 and an ARDL approach, the results reveal distinct short-run and long-run dynamics. In the short run, higher interest rates and exchange rate depreciation significantly reduce green investment, while global oil prices initially exert a positive influence before turning negative in subsequent periods. In the long run, exchange rates and global oil prices have a positive and significant effect on green investment, whereas interest rates are not statistically significant. These findings indicate that green investment is more responsive to external factors than domestic monetary policy over longer horizons. This study contributes to the limited empirical evidence on green finance in emerging markets by jointly examining monetary and external determinants within a unified framework. The results highlight the importance of exchange rate stability and energy transition strategies in supporting the development of sustainable financial markets in Indonesia.